Data from: Maximum cardiac performance of Antarctic fishes that lack haemoglobin and myoglobin: exploring the effect of warming on nature's natural knockouts - Egginton, Stuart; Axelsson, Michael; Crockett, Elizabeth L.; O'Brien, Kristin M.; Farrell, Anthony P. (Zenodo, 2020)
Comparisons among related species provide valuable insight into the functional consequences of natural genetic mutations. We assessed cardiac function at ambient and elevated temperatures in Antarctic notothenioids with contrasting levels of the oxygen binding proteins, haemoglobin (Hb) and myoglobin (Mb), to elucidate changes in cardiac performance that may compensate for impaired O2 transport. Notothenia coriiceps (Hb+Mb+) at 1oC had the highest maximum cardiac work rate (WC) and pressure generating capacity, but lowest relative ventricular mass and maximum cardiac output (Q̇) when compared with two icefish species, Chionodraco rastrospinosus (Hb-Mb+) and Chaenocephalus aceratus (Hb-Mb-). Cardiomegaly associated with absence of Hb generated an exceptionally large maximum stroke volume (VS) and Q̇, but a lower WC. However, C. rastrospinosus had a larger ventricle, a higher intrinsic heart rate (fH), and greater maximum VS and Q̇ than C. aceratus, suggesting that cardiac Mb has functional relevance. Warming to 4oC increased fH, but only increased maximum Q̇ in icefishes, while maximum WC and pressure development increased in N. coriiceps (both ~2.5x that of C. aceratus). The Hb+Mb+ myocardium generated considerable Q̇ against raised afterload, unlike icefish hearts. The presence of Hb and Mb enhances cardiac performance, and likely resilience to near-future ocean warming. Antarctic fish in situ heart data_Egginton et al. Data for in situ heart performance and morphometrics of fish used Funding provided by: National Science Foundation Crossref Funder Registry ID: http://dx.doi.org/10.13039/100000001 Award Number: ANT 1341602 and ANT 1341663